Writing tools 55 essentials strategies for every writer - Clark,Roy Peter (Little, Brown and Company, 2016)
Roy Peter Clark distills decades of experience into 50 tools that will help any writer become more fluent and effective. This book covers everything from the most basic ("Tool 5: Watch those adverbs") to the more complex ("Tool 34: Turn your notebook into a camera") and provides more than 200 examples from literature and journalism to illustrate the concepts. For students, aspiring novelists, and writers of memos, e-mails, PowerPoint presentations, and love letters, here are 50 tools.